Behavioral intention to use electronic cigarettes in the Philippines: The role of social influence, knowledge, price and health impact - Zachariah John A. Belmonte; Yogi Tri Prasetyo; Pamela Eyre R. Victoria; Maela Madel L. Cahigas; Reny Nadlifatin; Ma. Janice J. Gumasing (PLoS ONE, 2025)
Electronic cigarettes or e-cigarettes have gained significant popularity as an alternative to traditional cigarettes, yet limited research has examined the factors influencing their adoption, particularly in developing nations like the Philippines, where usage is rising. This study investigates the behavioral drivers of e-cigarette use, with a particular focus on the role of knowledge, alongside social influence, perceived price impact, perceived health impact, and perceived usefulness. Using purposive sampling, 310 valid responses were collected from current e-cigarette users, traditional cigarette users, or individuals with prior experience with these products. A structured questionnaire with 21 indicators was administered, and data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). The findings reveal that knowledge is the strongest predictor of behavioral intention, highlighting the critical role of informed awareness about the risks and impacts of e-cigarettes in shaping user decisions. Social influence, perceived price impact, and perceived health impact also significantly influence behavioral intention, demonstrating the interconnectedness of cognitive, social, and economic factors. Interestingly, perceived usefulness did not have a significant effect, challenging assumptions about the importance of functional benefits in driving e-cigarette adoption. These results underscore the importance of education and awareness campaigns in addressing misconceptions about e-cigarettes. Policymakers, regulators, and health professionals should prioritize knowledge-driven interventions to empower individuals to make informed decisions and mitigate e-cigarette use, particularly among younger and economically vulnerable populations.